(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent year, the brain imaging techniques has continually played an essential role in inspecting and concentrating on new visions of anatomy and brain functions. The image processing mechanism is extensively used in medicine to enhance early detection and treatment. Segmentation and classification is vital role for MRI brain image processing. The aim of this work is to develop a system that helps in tumour detection and brain MRI image recognition through the process of the proposed image classifier. In this work, we recommend a Deep Neural Network for classification and segmentation. This work proposes an image compression technique using a Deep Wavelet Auto encoder (DWA) that combines the ability to minimize the primary function of automatic encoders with the image degradation property of the wavelet transform. The combination of the two has an essential impact on reducing the size of the function set to withstand in addition classification tasks with DNN. A brain system has been eliminated and the proposed DNN- DWAE image classification is considered. The performance evaluation for the DNN- DWAE classifier has been improved compared with different existing method.